The Performance of Bamboo Truss with Gapit Form Under Vertical Loads - Amelia Shafa Kartika; Yulianto Purwono Prihatmaji (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2023)
The connection in bamboo construction is frequently the weakest point. This research discusses the performance of the gapit form on bamboo truss that effectively optimises the bamboo's inherent strength and can sustain vertical loads. Gapit is a connection form where a member is located between two members which also serves as a construction reinforcement. This truss optimizes the strength of whole bamboo with a total span of 4 meters and height of 2 meters. The gapit form applied at the top chord member, bracing member, and